Development and Validation of a Questionnaire to Measure Medication Adherence to Direct-Acting Agents in Patients with Hepatitis C - Adina Turcu-Stiolica; Irina Paula Doica; Bogdan Silviu Ungureanu; Ion Rogoveanu; Dan Nicolae Florescu; Mihaela-Simona Subtirelu; Dan Ionut Gheonea (Pharmaceutics, 2021)
This study aims to develop a new self-report tool (HCV-AD) measuring adherence factors, intentional or unintentional, during Hepatitis C Virus (HCV) treatment with direct-acting antivirals (DAA) aiming to achieve high efficacy, otherwise resulting in drug resistance and treatment failure. Two phases were conducted: in the first phase, items were generated based on an extensive literature review, and, in the second phase, a prospective cohort study was conducted using HCV patients from Gastroenterology Department from University County Hospital of Craiova, Romania (n = 222), to evaluate the validity and reliability of the questionnaire. A number of 19 items were generated following a systematic review and through expert opinion. The internal consistency reliability was evaluated using Cronbach’s alpha. The construct validity was assessed using correlations with two other instruments: visual analog scale (VAS) and medication possession ratio (MPR). The final questionnaire (HCV-AD10) was derived through exploratory factor analysis, with 82% of total variance explained. This instrument appeared as a reliable and valid measure for medication adherence, with Cronbach’s alpha (0.867) and significant high positive correlations between adherence scores calculated with HCV-AD10 and VAS (ρ = 0.61, p < 0.001) or with HCV-AD10 and MPR (ρ = 0.75, p < 0.001). This research would make a worthwhile contribution to HCV management.